ECTOPIC THYMUS IN CHILDREN: PREVALENCE, DIAGNOSIS AND CLINICAL SIGNIFICANCE - Алена Владимировна Ведерникова; Юрий Иванович Ровда; Наталья Николаевна Миняйлова; Ольга Валерьевна Шмакова; Татьяна Сергеевна Хоботкова; Наталья Степановна Черных; Иван Константинович Халивопуло; Ирина Николаевна Сизова; Андрей Владимирович Шабалдин; Яна Вячеславовна Юнкина; Олеся Сергеевна Сухарева (The Publishing House Medicine and Enlightenment, 2023)
Thymic tissue ectopia was more commonly identified by morphologists at the beginning of the 20th century, but publications about the significance of these inclusions appeared only in the 21st century. With the improvement of diagnostic technologies, previously considered as rudimentary foci, ectopic areas of the thymus began to be considered as part of a full-fledged organ, which are equally invaluable for the formation of the immune system. This review considers modern ideas about embryogenesis, prevalence, diagnosis and clinical significance of thymus ectopia both in healthy children and those who underwent thymectomy due to surgery for congenital heart defects.